Indirect monitoring method of tool wear using the analysis of cutting force during dry machining of Ti alloys - Sevilla-Hurtado, Lorenzo; Sanchez, Yezika; Trujillo-Vilches, Francisco Javier; Marcos, Mariano (My University, 2017)
In recent decades, optimize tool life is in constant evolution so many researchers have focused to analysis the tool wear by indirect monitoring (e.g. acoustic emission, cutting forces, vibrations) that plays a significant role in control and improvement of product during of machining operations - in real time to prevent instabilities of process. On another hand, it is recalled that titanium alloys are used in many industries as aerospace sector that have been utilized in strength to weight ration reduction in some parts of aircraft. On the negative side, Ti alloys tends to be hard machining due to their mechanical properties such as low thermal conductivity and modulus of elasticity causing increase cutting temperature, tool breakage or possibility interruption of process.
Keywords: Titanio - Aleaciones; Ciencia de los materiales; Titanium alloys; Chip morphology